Treatment with either leflunomide or adalimumab reduces anaemia in patients with rheumatoid arthritis - Ione C.P. Pereira; Nágila C.F. Sousa; Domingos M.S. Pereira; Saulo J.F. Mendes; Thayanne F. Muniz; Valderlane L.P. Colares; Bruna L.R. Silva; Cinara R.A.V. Monteiro; Mahiba M.R.S. Martins; Anita M.R. Fernandes; Elizabeth S. Fernandes (Anais da Academia Brasileira de Ciências, 2018)
ABSTRACT Rheumatoid arthritis is a chronic disease of the joints, which causes joint pain and disability. Anaemia is a frequent extra-articular manifestation in rheumatoid arthritis, affecting 30-70% of the patients; presenting a negative impact on patient´s quality of life. Some of the drugs used in rheumatoid arthritis treatment improve anaemia; but little is known on the beneficial effects of the anti-rheumatic leflunomide or the anti-TNFα adalimumab, in this parameter. We investigated the incidence of anaemia in rheumatoid arthritis patients treated or not with leflunomide or adalimumab. We also assessed whether anaemia correlates with disease activity. Anaemia was present in patients who had just been diagnosed with rheumatoid arthritis and had never taken disease modifying agents or biologicals (non-specific therapy group), but not in those taking either leflunomide or adalimumab. The erythrocyte sedimentation rate was increased in patients with non-specific therapy in comparison with those taking either leflunomide or adalimumab. Anaemia correlated with increased erythrocyte sedimentation rate. We suggest that leflunomide and adalimumab may be useful in treating anaemia in patients with rheumatoid arthritis.